N-terminal fragment of B-type natriuretic peptide predicts coexisting subclinical heart and vessel disease. Issue 10 (October 2017) - Pastormerlo, Luigi E.; Maffei, Stefano; Latta, Daniele Della; Chubuchny, Vladislav; Susini, Carla; Berti, Sergio; Prontera, Concetta; Storti, Simona; Passino, Claudio; Pasanisi, Emilio; Emdin, Michele; Chiappino, Dante
Abstract : Background: Identification of preclinical cardiovascular disease represents a challenge. We evaluate N-terminal proB-type natriuretic peptides (NT-proBNP) as markers of both cardiac and vascular subclinical disease in a community-based study including asymptomatic middle- aged study participants. Methods and results: In total, 807 study participants without previous cardiovascular disease were recruited. They underwent thorough laboratory assessment (including NT-proBNP), ultrasound examination of heart and evaluation of coronary calcium score and carotid intima-media thickness, by computed tomography and ultrasound, respectively. Cardiac and vascular disease were defined as one among left ventricular (LV) ejection fraction less than 50% (3.1%), E/E' ratio more than 15 (9%), LV mass index more than 115 in men or more than 95 g/m 2 in women (20%), LV end diastolic diameter more than 55 mm (2.5%), coronary calcium score more than 100 AU (13%), or carotid intima-media thickness more than 1.2 mm (21%), respectively. NT-proBNP [OR, 1.275; 95% (confidence interval) CI, 1.007–1.613, P  < 0.001], 10-year Framingham risk score (FRS; OR 1.132; 95% CI, 1.058–1.212, P  < 0.001) and lower creatinine clearance (OR, 0.983; 95% CI, 0.971–0.994, P  < 0.001) predicted cardiac (220, 27%), whereas 10-year Framingham risk score (OR, 1.340; 95% CI, 1.245–1.674, P  < 0.001) and NT-proBNP (OR, 1.501; 95% CI, 1.181–1.907, P  < 0.001) predicted vascular involvement (215, 26%), at multivariate analysis. In total, 84 study participants (10.1%) had coexisting cardiac and vascular disease. NT-proBNP increased linearly from health study participants to study participants with only cardiac or vascular involvement, up to coexisting cardiovascular disease. Conclusion: Coexisting cardiac and vascular involvement in asymptomatic study participants is common. Along with traditional risk factors, NT-proBNP appears a valuable biomarker for global subclinical heart and vessels disease.